Integrating Renewable Energy Systems: Exploring New Approaches to Hybrid Renewable Energy Generation - Taher Abdallah Ali Galouz; Mustafa Ahmed Benhkoma (African Journal of Advanced Pure and Applied Sciences, 2023)
The increasing demand for clean and sustainable energy has led to the exploration of innovative solutions for integrating renewable energy systems. Hybrid renewable energy generation, which combines multiple renewable sources, offers a promising approach to achieving a reliable and efficient power supply. This research explores the concept of hybrid renewable energy generation, highlights the benefits of integration, and discusses new approaches and technologies being developed to optimize hybrid systems. The study concluded that Solar photovoltaic (PV) and (WGT) wind power systems have emerged as key contributors to the global transition towards renewable energy sources. HRES is now gradually being employed for the electrification of rural areas due to the cheaper cost of Wind Turbine (WGT) and Solar Photovoltaic (SPV). It is intended to support the provision of electricity for the more than a billion people in developing nations who lack access to it. Using HRES in place can boost power dependability.